Land reform in Zimbabwe: the narrative and counter-narrative of traditional leaders' role on land tenure and governance in rural and A1 model settlements- period 1980 to 2014 - Karanda, Crispen Zindoga (My University, 2016)
This project employs a narrative and counter narrative lens to seek an understanding of the changing roles of traditional leaders in an independent Zimbabwe. A historical context was necessary in order to highlight changes in traditional leadership roles prior to the independence era. This process of using the historical context facilitated a discussion that was divorced from biases associated with colonialism and independence. To achieve this, a study was undertaken of the period prior to the colonial era, within the colonial era and post colonial period. This resulted in a rich discussion of the changing roles within each period together with implications to traditional leadership in an independent Zimbabwe. The study undertook a detailed review that provided the basis for the placement into the historical context that was supported by academic literature. The use of theory further consolidated the placement of the study in an academic context. Data collection and analysis were placed in narrative and counter narrative contexts using a thematic approach to find meaning to the study while addressing assertions that were raised in the study. The findings proved that traditional leaders in Zimbabwe have lost their powers and are partaking of new modern roles slowly divorced from the traditional context of both the pre and colonial era. It also proved that traditional leaders are aware of the changing roles and might be enjoying the benefits of the modern system at the expense of both tradition and culture. The other argument however is that traditional role conflicts with democratic processes and may not really be representative of a democratic government as these leaders are not elected. The findings of this study should highlight to the traditional leaders of the irreversible changing roles which only stand to maintain what could be an oppressive system similar to the colonial era unless it is checked and controlled. The study may also help academics and other interested parties that may be advocating for a separation of African systems in place of Western influenced governance despite the globalised nature of the world that maybe considered a disadvantage to poor countries.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Political Science to the Faculty of Political Science, University of the Witwatersrand, Johannesburg, 2016
Keywords: Land tenure--Zimbabwe--History; Land tenure--Political aspects--Zimbabwe; Zimbabwe--Politics and government